A Network Approach to the Five-Facet Model of Mindfulness: Insights from Gaussian Graphical and Directed Acyclic Graph Models - Alexandre Heeren; Séverine Lannoy; Charlotte Coussement; Yorgo Hoebeke; Alice Verschuren; Annelise Blanchard; Nadia Chakroun-Baggioni; Pierre Philippot; Fabien Gierski (Open Science Framework, 2022)
Despite the large-scale dissemination of mindfulness-based interventions, debates persist about the very nature of mindfulness. To date, one of the dominant views is the five-facet approach, which suggests that mindfulness includes five facets (i.e., Observing, Describing, Nonjudging, Nonreactivity, and Acting with Awareness). However, uncertainty remains regarding the potential interplay between these facets. In this study, we investigated the five-facet model via network analysis in an unselected sample (n = 1,704). We used two distinct computational network approaches: a Gaussian graphical model (i.e., undirected) and a directed acyclic graph, with each model determining the relations between the facets and their relative importance in the network. Both computational approaches pointed to the facet denoting Acting with Awareness as playing an especially potent role in the network system. Altogether, our findings offer novel data-driven clues for the field's larger quest to ascertain the very foundations of mindfulness.
Keywords: clinical psychology; five-facet model of mindfulness; mindfulness; network analysis